2015
DOI: 10.1021/mp500628g
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor-Targeted Multimodality Imaging of Ovarian Cancer in a Novel Syngeneic Mouse Model

Abstract: A new transplantable ovarian tumor model is presented using a novel folate receptor (FR) positive, murine ovarian cancer cell line that emulates the human disease and induces widespread intraperitoneal (i.p.) tumors in immunocompetent mice within 4–8 weeks of implantation. Tumor development was monitored using a new positron emission tomography (PET) FR-targeting reporter with PET/computerized tomography (PET/CT) and fluorescence molecular tomography (FMT) using a commercial FR-targeting reporter. Conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Folic acid can conjugate with folate receptor (FR), which is overexpressed in many types of tumors including ovarian, endometrial, breast, renal cell carcinomas, and so forth. Targeting the folate receptor has shown considerable promise in mediating uptake of a variety of drugs, gene therapy products, and radiopharmaceuticals …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid can conjugate with folate receptor (FR), which is overexpressed in many types of tumors including ovarian, endometrial, breast, renal cell carcinomas, and so forth. Targeting the folate receptor has shown considerable promise in mediating uptake of a variety of drugs, gene therapy products, and radiopharmaceuticals …”
Section: Introductionmentioning
confidence: 99%
“…Targeting the folate receptor has shown considerable promise in mediating uptake of a variety of drugs, gene therapy products, and radiopharmaceuticals. [12][13][14] Therefore, we have explored a new folic acid-conjugated PEG-PLA micelle delivery system for HB (HB/FA-PEG-PLA micelle). In the present study, the stability and drug release of the HB/FA-PEG-PLA micelles either in vitro or in vivo were studied.…”
mentioning
confidence: 99%
“…Notably, this agent is capable of delineating the metastatic spread of OVCAR3 tumors along the ipsilateral chain of lymph nodes. Ocak et al recently used a 68 Ga-DOTA-albumin–folate conjugate and FR680 for the multimodal PET/fluorescence molecular tomographic imaging of the intraperitoneal spread of folate receptor–positive MKP-L cells (25). Similarly, Liu et al reported on the multimodal PET/optical imaging of metastatic ovarian tumors within the peritoneum of mice using a 64 Cu-labeled pyropheophorbide–folate conjugate (26).…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…To limit the potential damage caused by these treatments, targeting-based cancer treatments have become alternatives [1]. Certain receptors and transporters, such as folate receptors [2][3][4][5][6][7][8][9][10][11][12][13][14], glucose transporters [15][16][17], transferrin receptors (TfR) [18][19][20][21] and riboflavin (RF) receptors [22][23][24][25], are highly overexpressed on the surface of certain cancer cells. Thus, these receptors can be used as target sites when employing targeting-based cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, folate receptors are overexpressed on the cell membrane of ovarian [2], cervical [3], breast [4], lung [5], kidney [6], colon/rectum [7] and brain tumor cells [8]. Thus, folate receptors have been used as targets in studies on drug delivery [9,10] and cell imaging against these target cancer cells [11][12][13][14]. In addition, Warburg effect describes the phenomenon that cancer cells consume a larger amount of glucose and have a higher aerobic glycolysis rate than normal cells [15,16].…”
Section: Introductionmentioning
confidence: 99%